EFEKTIVITAS MEDIA POWER POINT INTERAKTIF DALAM MENINGKATKAN PRESTASI BELAJAR IPAS SISWA KELAS III SEKOLAH DASAR - Widyorini, Septy; Hermawan Wahyu Setiadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to: 1) determine the differences in students’ learning achievement in IPAS between the use of interactive PowerPoint media and picture media among third-grade students at SD Muhammadiyah Ambarbinangun, and 2) examine the effectiveness of interactive PowerPoint–based learning media on the IPAS learning achievement of third-grade students at SD Muhammadiyah Ambarbinangun. This study employed a quantitative approach with a quasi-experimental design of the nonequivalent control group type. The research was conducted at SD Muhammadiyah Ambarbinangun by involving two classes, namely class III A as the control group using picture media and class III B as the experimental group using interactive PowerPoint media. Data were collected through pretest and posttest using test instruments developed based on IPAS learning indicators. The data were analyzed using descriptive statistics to identify students’ initial and final learning achievement, followed by prerequisite analysis and a t-test to determine differences in learning achievement between the two groups. The results of the study indicate that: 1) there is a difference in IPAS learning achievement between students who used interactive PowerPoint media and those who used picture media. The mean posttest score of the experimental group was higher (80.00) than that of the control group (67.89), with a significance value of 0.014 < 0.05; and 2) interactive PowerPoint media are proven to be effective in improving IPAS learning achievement, as indicated by an N-Gain score of 0.68 in the moderate category. Therefore, the use of interactive PowerPoint media effectively improves the IPAS learning achievement of third-grade students.